2019
DOI: 10.1016/j.csbj.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering plasmid maintenance factors for computational plasmid design

Abstract: Plasmids are genetic parasites of microorganisms. The genomes of naturally occurring plasmids are expected to be polished via natural selection to achieve long-term persistence in the microbial cell population. However, plasmid genomes are extremely diverse, and the rules governing plasmid genomes are not fully understood. Therefore, computationally designing plasmid genomes optimized for model and nonmodel organisms remains challenging. Here, we summarize current knowledge of the plasmid genome organization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 187 publications
2
19
0
Order By: Relevance
“…The shuttle vector pMMGK brings new proteins (RepA, RepB, RepC, eGFP and Kan R ) and new RNAs to C. burnetii . The potential effects of these proteins and RNAs on bacterial physiology are impossible to predict (25, 26). The RSF1010 ori -based shuttle vectors are commonly used for C. burnetii transformation (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…The shuttle vector pMMGK brings new proteins (RepA, RepB, RepC, eGFP and Kan R ) and new RNAs to C. burnetii . The potential effects of these proteins and RNAs on bacterial physiology are impossible to predict (25, 26). The RSF1010 ori -based shuttle vectors are commonly used for C. burnetii transformation (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…This allows more accurate comparisons between the evolutionary host range and replication/transfer host range of the plasmid. In addition, various factors have been found that determine or affect the host range of a plasmid within itself and/or in its host chromosome, including DNA polymerase, helicase, gyrase, and nucleoid associated proteins involved in the capability of replication, maintenance, and/or conjugation of a plasmid (Shintani et al, 2015;Shintani and Suzuki, 2019;Yano et al, 2019). Therefore, it is necessary to consider the absence or presence of these factors on the plasmid or chromosomes for the prediction of plasmid host range.…”
Section: Comparisons Of Predicted Hosts Of Psn1216-29 With Experimentally Obtained Transconjugantsmentioning
confidence: 99%
“…In summary, our use of both deletion and synthetic biology approaches (35) in this study revealed a unique and novel feature of IncP-9 plasmids in that mpfK and kikA pWW0 are indispensable for the conjugative transfer of the two IncP-9 plasmids. On the other hand, R751 and R388 did not require the MpfK-like proteins for their conjugative transfer.…”
Section: Discussionmentioning
confidence: 80%